2019
DOI: 10.1101/801480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Malaria parasite immune evasion and adaptation to its mosquito host is influenced by the acquisition of multiple blood meals

Abstract: 14A minimum of two blood meals are required for a mosquito to acquire and transmit 15 malaria, yet Anopheles mosquitoes frequently obtain additional blood meals during their 16 adult lifespan. To determine the impact of subsequent blood-feeding on parasite 17 development in Anopheles gambiae, we examined rodent and human Plasmodium 18 parasite infection with or without an additional non-infected blood meal. We find that an 19 additional blood meal significantly reduces P. berghei immature oocyst numbers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
2
10
1
Order By: Relevance
“…Oocysts can take up labelled mosquito lipoparticles [ 36 ], and increased availability of lipids as provided by an additional blood meal may accelerate host lipid scavenging, which also occurs during human stages of infection [ 37 39 ]. In this study, however, depletion of Lp—the major mosquito lipid transporter—did not slow rates of oocyst growth or sporozoite appearance after a second blood feeding, with only a slight, non-significant delay in EIP 50 detected, suggesting that other nutrients (possibly amino acids, as suggested by a recent report [ 21 ]) may mediate the bulk of the observed boost in oocyst development. Lp silencing also had no effects on P .…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Oocysts can take up labelled mosquito lipoparticles [ 36 ], and increased availability of lipids as provided by an additional blood meal may accelerate host lipid scavenging, which also occurs during human stages of infection [ 37 39 ]. In this study, however, depletion of Lp—the major mosquito lipid transporter—did not slow rates of oocyst growth or sporozoite appearance after a second blood feeding, with only a slight, non-significant delay in EIP 50 detected, suggesting that other nutrients (possibly amino acids, as suggested by a recent report [ 21 ]) may mediate the bulk of the observed boost in oocyst development. Lp silencing also had no effects on P .…”
Section: Discussioncontrasting
confidence: 52%
“…These findings are consistent with infection studies in closely related mosquito species that showed that an additional blood meal during development either boosts P . falciparum sporozoite intensities or yields [ 22 26 , 34 ] or increases oocyst size [ 21 23 ], although none analyzed parasite growth rates after the second meal. Our study conclusively links the effects of an additional blood meal to increased parasite developmental rates and a shortened EIP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effects of 20E on mosquito immunity and reproductive fitness potentially depend on specific host-pathogen interactions that define differences in An. gambiae immunity to P. berghei and P. falciparum parasites (45,61). In summary, our findings demonstrate the role of the hormone 20E in priming mosquito innate immunity to both bacteria and malaria parasites.…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, the effects of 20E on mosquito immunity and reproductive fitness potentially depend on specific host-pathogen interactions that define differences in An. gambiae immunity to P. berghei and P. falciparum parasites [60,75].…”
Section: Discussionmentioning
confidence: 99%